Estimation of the state of proliferative activity and expression of the oncomarker p53 in samples of actinic keratosis. - Hlushok, V. S.; Sviatenko, T. V.; Shponka, I. S.; Poslavska, O. V. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Actinic keratosis is a precancerous condition of the skin, which most often occurs in the open areas of the skin (primarily, the head, neck and extremities) after prolonged or intense natural or artificial irradiation by ultraviolet rays in genetically predisposed people and is very common in light-age patients of middle and advanced age. The untreated actinic keratosis progresses to squamous cell carcinoma of the skin from 5% to 10% of cases. Objective. The aim of the study was to compare the proliferative activity and the different options of the p53 oncomarker expression in different forms and degrees of histological severity of actinic keratosis and, separately, with the observations of seborrheic keratosis to improve the quality of differential-diagnostic immunomorphological criteria. Methods. A prospective immunohistochemical study of 24 skin samples was carried out: 15 actinic keratoses (3 hypertrophic, 2 pigmented, 10 proliferative forms) and 9 seborrheic keratoses, for comparison of histological characteristics and immunomorphological profile according to Ki-67, p53, cyclin D1 markers. Results. The authors distinguished the significant histological characteristics of actinic and seborrheic keratoses, calculated the proliferation indices for Ki-67 and cyclin D1, and also analyzed the expression of the oncoprotein p53 in comparison groups. Conclusion. An analysis of the similarity of the AK and SC collections with the Fisher’s exact test showed a difference only in the expression of the markers p53 and Ki-67 (pp53 = 0.00682 (C = 0.514), pki-67 = 0.00202, (C = 0.548) respectively).